A bibliometric analysis of sleep in older adults - Liu, Haitao; Liu, Feiyue; Ji, Haoyuan; Dai, Zuanqin; Han, Wenxiu (Frontiers in Public Health, 2023)
Background: Sleep problems severely affect the quality of life in the elderly and have gradually gained attention among scholars. As a major hot spot of current research, sleep in older adults is highly exploratory and of great significance for human health. Objective: Therefore, in this study, the current state of the art of sleep research in older adults was analyzed through the visual mapping function of CiteSpace software. Using this software, we analyzed popular research questions and directions and revealed the development trends and research frontiers of this field. Methods: In this paper, we searched the Web of Science database for sleep-related studies focusing on older adults and analyzed the number of publications, journals, authors, institutions, country regions, and keywords by using CiteSpace software. Results: Our results revealed that the number of publications concerning sleep in older adults has gradually increased; after 2017, this field underwent rapid development. The journal Sleep has published the majority of the articles on sleep in older adults and has the highest citation frequency. The Journal of the American Geriatrics Society has the highest impact factor and CiteScore among the top 10 journals in terms of the number of published articles. The United States has the highest number of publications and most of the leading institutions in this field are located in the United States, with the University of California, Los Angeles, and the University of Pittsburgh having the highest number of publications. Dzierzewski JM is the most published author and has played an important role in guiding the development of this field. Research in this area is focused on insomnia, sleep quality, depression, and sleep duration. Conclusion: The rapid development of sleep research in older adults, which shows a yearly growth trend, indicates that this field is receiving increasing attention from researchers. Insomnia in older adults is the most concerning problem in this field. At the same time, future research should continue to focus on the impact of sleep disorders on older adults to improve sleep and quality of life in older adults.